Juvenile xanthogranuloma. - Mazzotta, F. (European Journal of Pediatric Dermatology, 2009)
A 40-day-old boy was first observed due to two nodules, one on the left frontoparietal region (Fig. 1), the other on the left elbow (Fig. 2), present since birth and rapidly growing. The first nodule, gross-ly hemispheric, 1 centimeter in size, was ulcerated. The second one, 0.8 x 0.5 cm, irregularly shaped, was yellowish. The clinical diagnosis was juvenile xanthogranuloma. An ophthalmological examination ruled out involvement of the eye. The frontoparietal nodule was removed on his mother's request. The histological examination, showing a proliferation of partially lipidized histiocytes and Touton cells (Fig. 3 and box), confirmed the clinical diagnosis of juvenile xanthogranuloma. After removal xanthogranuloma partially recurred (Fig. 4).